MERANCANG MODEL BISNIS YANG TEPAT UNTUK USAHA KECILSEBAGAI PANDUAN KEGIATAN OPERASIONAL STUDI KASUS PADA USAHA GERAI “KING MONSTER”FRIED CHICKEN - Petrus Pius Salamin; Francisca Hermawan (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2019)
Abstract, This article aims to (1) design an appropriate business model for a small business, (2) give an example of business model that may be can be applied to the same kind of business or other small businesses, (3) give a guidance to the owner and employee in daily operational activity.This aricle is based on the survey result at King Monster Fried Chicken Outlet (gerai), and survey at the area sorounded. It is also based on interview with the owner of the business and literature study. Having analysed all the data and information, and then try to describe what kind of business model would be appropriate for a small business.It can be concluded that a Canvas Businees Model is an appropriate business model for a small business.